Transforming Conservation Landscapes: Participatory Approaches and Community Belonging in Restoration Projects in Georgia - Mikeladze, Aleksandre (European Journal of Social Science Education and Research, 2026)
This paper examines the intersection of conservation practice, community participation, and belonging through a case study of SABUKO (Society for Nature Conservation) in Georgia. Drawing on documentary analysis of multiple conservation initiatives, including grassland restoration in the Kakheti steppes, landscape connectivity planning, and youth empowerment initiatives, the study explores how environmental organizations can either reproduce or challenge existing power structures that determine who belongs in conservation spaces. The findings reveal recurring relationship between expert-driven and community-centered approaches, and highlight the importance of creating genuinely inclusive governance mechanisms. SABUKO’s evolving practice, shifting from species-focused interventions to integrated landscape restoration with socio-economic dimensions, offers insights for conservation organizations seeking to balance ecological and social equity objectives.